Implementation of Serial Workshop by Students Educational Need: Trend to Accountability in Medical Education (Bangladesh Journal of Medical Science, 2018)
Introduction: The aim of this study was to assess professors’ and students’ educational needs and implementation of serial workshops and then evaluate the effect of these educational workshops on the knowledge and practice of medical students.Method: Students’ educational needs and the clinical professors’opinion were used tocomplete the needs assessment process.120 Medical students participated in serial workshops. This program was applied to develop educational accountability program. In each workshop, students’ knowledge was evaluated by valid and reliable multiple-choice questions before andafterthe course. In some workshops, their performance was measured by the OSCE test.Descriptive analysisandpaired t- test were used to evaluate difference in students’ mean score.Finding: Results of before and after series of workshops in various areas revealed that workshop programs had a significant impact on the promotion of students’ knowledge (The mean score of students before and after workshops). Then,the evaluation of theirperformance through the OSCEtest was significant(P